Cross-cultural adaptation and validation of the Kerlan-Jobe Orthopaedic Clinic shoulder and elbow score in Finnish-speaking overhead athletes - Maria Sukanen; Jesse Pajari; Sami Äyrämö; Juha Paloneva; Benjamin Waller; Arja Häkkinen; Juhani Multanen (BMC, 2022)
Abstract Background The Kerlan-Jobe Orthopaedic Clinic Shoulder and Elbow score (KJOC) is developed to evaluate the shoulder and elbow function in overhead athletes. To date, the score has not been adapted into Finnish language. The aim of this study was to perform a cross-cultural adaptation of the Kerlan-Jobe Orthopaedic Clinic Shoulder and Elbow score (KJOC) into Finnish language and evaluate its validity, reliability, and responsiveness in overhead athletes. Methods Forward-backward translation method was followed in the cross-cultural adaptation process. Subsequently, 114 overhead athletes (52 males, 62 females, mean age 18.1 ± 2.8 years) completed the Finnish version of KJOC score, Disabilities of the Arm, Shoulder and Hand (DASH), American Shoulder and Elbow Surgeons Standardized Shoulder Assessment Form (ASES) and RAND-36 to assess validity of the KJOC score. To evaluate reliability and responsiveness, the participants filled in the KJOC score 16 days and eight months after the first data collection. Validity, reliability, and responsiveness of the Finnish KJOC score were statistically tested. Results Minor modifications were made during the cross-cultural translation and adaptation process, which were related to culture specific terminology in sports and agreed by an expert committee. Construct validity of the KJOC score was moderate to high, based on the correlations with DASH (r = − 0.757); DASH sports module (r = − 0.667); ASES (r = 0.559); and RAND-36 (r = 0.397) questionnaires. Finnish KJOC score showed excellent internal consistency (α = 0.92) and good test-retest reliability (2-way mixed-effects model ICC = 0.77) with acceptable measurement error level (SEM 5.5; MDC 15.1). Ceiling effect was detected for asymptomatic athletes in each item (23.2-61.1%), and for symptomatic athletes in item 5 (47.4%). Responsiveness of the Finnish KJOC score could not be confirmed due to conflicting follow-up results. Conclusion The Finnish KJOC score was found to be a valid and reliable questionnaire measuring the self-reported upper arm status in Finnish-speaking overhead athletes.